Implementation of a digital voltmeter with integrated voice - Tejada Muñoz, Guillermo (2012)
This article describes the results of a research study conducted at the Institute for Research of the Faculty of Electronic and Electrical Engineering of the UNMSM. Following the focus of the study was implemented a digital voltmeter DC, which issues through a loudspeaker a voice that informs the user of the amount of volts that the voltmeter is measuring. The methodology is based on the digitization of the voice that is stored in a serial EEPROM memory, microcontroller governs the process. Additionally, the measurement value can also be read through an LCD display.